Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.11564/28-0-548
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic correlates and the choice of treatment for childhood fever in Ghana

Abstract: The study investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
4
4
0
Order By: Relevance
“…The result also revealed that those caretakers from higher wealth seek more formal health care compared to the lower wealth. This is also similar to the studies done in Nepal, Cambodia, and Ghana [ 4 , 17 , 23 ]. This is mainly because caretakers need resources to get service from health facilities.…”
Section: Discussionsupporting
confidence: 91%
“…The result also revealed that those caretakers from higher wealth seek more formal health care compared to the lower wealth. This is also similar to the studies done in Nepal, Cambodia, and Ghana [ 4 , 17 , 23 ]. This is mainly because caretakers need resources to get service from health facilities.…”
Section: Discussionsupporting
confidence: 91%
“…This is because aging mothers might have given birth severally and hence have better experiences with regards to appropriate child health seeking behaviour relative to younger mothers. This finding is similar to the results of Arthur (2014) in the case of private or mobile clinics. The negative coefficient of birth order which was significant at 5% implied that increasing birth order decreased the likelihood of children being sent first to a government health facility relative to self-medication/traditional source.…”
Section: Regression Analysissupporting
confidence: 90%
“…Thus maternal insurance increases the likelihood of seeking care for children with fever or cough initially from government health facilities. This is similar to the findings on Ghana by Arthur (2014) Mothers with big problems in getting permission to seek selfmedical care were revealed to be more likely to first resort to selfmedication/Traditional practitioners for childhood fever or cough relative to Private health facility or provider/field worker/mobile clinic/maternity home. Thus since mothers normally seek care for their children, if there are difficulties in securing permission to seek medical care for mothers, it would affect child health seeking behaviour negatively.…”
Section: Regression Analysissupporting
confidence: 87%
See 2 more Smart Citations